OP0165 A neoepitope fragment of c-reactive protein is prognostic of radiographic knee oa. (15th June 2017) - Bay-Jensen, AC; Bihlet, A; Byrjalsen, I; Andersen, JR; He, Y; Siebuhr, AS; Thudium, CS; Riis, BJ; Christiansen, CH; Karsdal, MA
Abstract : Background: There are two major needs in clinical development of DMOADs: 1) Identifying a suitable population with an active and progressive disease in order to demonstrate significant improvements by an efficacious intervention; and 2) Phenotyping patients and linking them to a corresponding treatment mode-of-action (e.g. anti-inflammatory). The biochemical marker CRPM is a neoepitope of C-reactive protein (CRP) and is released from the local inflamed tissue when CRP is degraded by proteases such as matrix metalloproteinases Objectives: The purpose of this study was to translate the CRPM, from rheumatoid arthritis (RA), where it has been extensively tested, to OA, and to test whether it is predictive of radiographic OA. Methods: The placebo arms of two phase III OA trial (clinicaltrial.gov: NCT00486434 and NCT00704847 ), a phase III RA study (the LITHE study, N=490), which included patients with active, moderate-severe RA (NCT00106535 ), as well as in an early RA cohort (N=92) were used. Subjects with symptomatic and radiographic knee OA: WOMAC pain ≥150mm and/or WOMAC function ≥510mm, and Kellgren-Lawrence grade (KLG) 2 or 3. KLG were scored for both knees at baseline and year 2 (Y2). Serum CRPM and hsCRP were measured at baseline. The association between serum CRPM levels and disease activity score (DAS28) and hsCRP was investigated by Spearman's correlations. Quartile ranges of CRPM in the early RA cohort were used to define the cut-off between inflammatory OA and non-inflammatory OA. OA knees were divided into cases and controls based on a terminology proposed by the FNIH-OAI consortium (1); knees with KLG≥2 at BL were excluded, and incidence OA at Y2 was defined KLG≥2. Logistic regression was used to compare cases and controls. Results: There was a significant correlation between disease activity measures and CRPM in both RA studies. Seventy-five percent of the LITHE patients had high or very high levels of CRPM at BL, which was changed to a pattern similar to early RA after treatment. The mean CRPM levels were significantly lower in OA (8.5 [95% CI 8.3–8.8] ng/mL) compared to the RA patients (15.6 [9.5–21.6] ng/mL); however, a significant subset of OA patients (41% and 31% in SMC2301 and SMC2302) had CRPM levels ≥9ng/mL, as 75% of patients with early RA. Patients with BL or Y2 CRPM levels ≥9ng/mL were more likely to develop knee OA than patients with low level of CRPM. Overall, moderate to very high levels of CRPM at BL and Y2 were predictive of incidence OA with odds ratio of 4.6 [1.2–17] and 2.5 [1.2–4.8]. Conclusions: A subset of OA patients, up to 41%, appear to have tissue inflammation comparable to that of RA, reflected by the level of CRPM. Furthermore, high CRPM levels was prognostic of incident knee OA. These data suggest that CRPM is blood-based biochemical marker for finding OA patients with an inflammatory phenotype. References: Longitudinal validation of periarticular bone area and 3D shape as biomarkers for knee OA progression? Data from the FNIH OA Biomarkers Consortium.Hunter D et al.Ann Rheum Dis. 2016 Sep;75(9):1607–14. Disclosure of Interest: A. Bay-Jensen Shareholder of: Nordic Bioscience, Grant/research support from: DBOARD, Employee of: Nordic Bioscience, A. Bihlet Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, J. Andersen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, Y. He Employee of: Nordic Bioscience, A. S. Siebuhr Employee of: Nordic Bioscience, C. Thudium Employee of: Nordic Bioscience, B. Riis Shareholder of: Nordic Bioscience, C. Christiansen Shareholder of: Nordic Bioscience, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience